Comparative analysis of the evolution of vegetable production between the period after 1989 revolution and the period when Romania joined European Union - Eduard Alexandru Dumitru (Agrarian Economy and Rural Development - Realities and Perspectives for Romania. 6th Edition of the International Symposium, November 2015, Bucharest, 2015)
Romanian agriculture has been subjected to cyclical periods difficult enough over a short period of time. After the passing of the revolution, Romania has traveled through a difficult process of transformation and the results were not observed or are not seen, the evolution of Romanian agriculture continued with the period before Romania joined EU, during this period of time agriculture received financial suport, that was named SAPARD, but without visible results on the agricultural sector. Most likely this range of 2014-2020, is the last train that can save Romanian agriculture, if it wouldn't be taken seriously we won't get another chance.
Keywords: 330; development of agriculture; the European Union; crop production